The first head‐tailed virus, MFTV1, infecting hyperthermophilic methanogenic deep‐sea archaea. (19th October 2020) - Thiroux, Sarah; Dupont, Samuel; Nesbø, Camilla L.; Bienvenu, Nadège; Krupovic, Mart; L'Haridon, Stéphane; Marie, Dominique; Forterre, Patrick; Godfroy, Anne; Geslin, Claire
Summary: Deep‐sea hydrothermal vents are inhabited by complex communities of microbes and their viruses. Despite the importance of viruses in controlling the diversity, adaptation and evolution of their microbial hosts, to date, only eight bacterial and two archaeal viruses isolated from abyssal ecosystems have been described. Thus, our efforts focused on gaining new insights into viruses associated with deep‐sea autotrophic archaea. Here, we provide the first evidence of an infection of hyperthermophilic methanogenic archaea by a head‐tailed virus, Methanocaldococcus fervens tailed virus 1 (MFTV1). MFTV1 has an isometric head of 50 nm in diameter and a 150 nm‐long non‐contractile tail. Virions are released continuously without causing a sudden drop in host growth. MFTV1 infects Methanocaldococcus species and is the first hyperthermophilic head‐tailed virus described thus far. The viral genome is a double‐stranded linear DNA of 31 kb. Interestingly, our results suggest potential strategies adopted by the plasmid pMEFER01, carried by M . fervens, to spread horizontally in hyperthermophilic methanogens. The data presented here open a new window of understanding on how the abyssal mobilome interacts with hyperthermophilic marine archaea.